Pola Komunikasi Keluarga Pada Model Helicopter Parenting (pada Anak Dalam Fase Late Adolescence) - Reynaldo, Rahmat; Prasetio, Arie (eProceedings of Management, 2024)
The role of the family in child development is very important because the family is the first social group in everyhuman being's life. In choosing and determining the level of college, a child needs the role of both parents to provideadvice and views regarding their choices. If children are not given freedom to express their opinions, they willwithdraw from their parents. The purpose of this study was to determine the communication patterns of families whohave a helicopter parenting pattern in choosing their children's level of college. The research method in this study isa qualitative method with a phenomenological approach. This study focuses on the conversation dimension in theFamily Communication Patterns theory. The results of this study are that the communication patterns of children andparents who have a helicopter parenting pattern have limitations, causing children to choose to be more open withothers. There should be openness, empathy, and mutual support in children and parents so that both children andparents are at an equal point in communicating without any feelings of not being heard for both parties, resulting ineffective communication in a family. Keywords-communication patterns, family communication, helicopter parenting, conversation.